2019
DOI: 10.1158/1535-7163.mct-19-0105
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Genomic Landscape in ALK+ NSCLC Patients Identifies Novel Aberrations Associated with Clinical Outcomes

Abstract: Rearrangements in the anaplastic lymphoma kinase (ALK) gene are found in approximately 5% of non-small cell lung carcinoma (NSCLC). Here, we present a comprehensive genomic landscape of 11 patients with ALKþ NSCLC and investigate its relationship with response to crizotinib. Using wholeexome sequencing and RNAseq data, we identified four rare ALK fusion partners (HIP1, GCC2, ERC1, and SLC16A7) and one novel partner (CEP55). At the mutation level, TP53 was the most frequently mutated gene and was only observed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 30 publications
0
14
1
Order By: Relevance
“…Biology pathways of proteins listed in Figure 2 C are shown in Figure 2 D and S2D. We also examined the expression of BCAT1 from publicly available datasets 5 , 32 , 33 and found that BCAT1 was expressed at higher levels (but not statistically significant presumably due to small sample size) in metastatic tissues compared to primary tissues in both proteomic and transcriptomic data ( Figure S3 A). To gain additional insights on the potential role of BCAT1 dysregulation in lung cancer, we utilized TCGA data and performed Kaplan-Meier survival analysis based on mRNA expression of BCAT1.…”
Section: Resultsmentioning
confidence: 99%
“…Biology pathways of proteins listed in Figure 2 C are shown in Figure 2 D and S2D. We also examined the expression of BCAT1 from publicly available datasets 5 , 32 , 33 and found that BCAT1 was expressed at higher levels (but not statistically significant presumably due to small sample size) in metastatic tissues compared to primary tissues in both proteomic and transcriptomic data ( Figure S3 A). To gain additional insights on the potential role of BCAT1 dysregulation in lung cancer, we utilized TCGA data and performed Kaplan-Meier survival analysis based on mRNA expression of BCAT1.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, t-MAD scores correlate with established molecular features of higher risk, i.e. with the presence of TP53 mutations and the EML4-ALK variant 3, which themselves portend worse survival, both in carefully controlled retrospective [ 5 , [54] , [55] , [56] ] and prospective trials [57] . While the EML4-ALK variant does not change during the disease, TP53 mutations do emerge under treatment, and their appearance is a marker of increased risk [6] .…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-four ALK fusion positive NSCLC patients were enrolled and administered crizotinib, with the aim of identifying prognostic proteomic and genomic biomarkers of response to crizotinib [19]. This study showed that there are likely multiple prognostic genomic biomarkers besides ALK mutations, that could be reflected in proteins other than ALK fusion-related protein products.…”
Section: Patient Characteristics and Clinical Outcomementioning
confidence: 99%